MULTIFRACTALITY AND COMPLEXITY OF THE BRAZILIAN AGRIBUSINESS COMMODITIES - JALE, Jader da Silva; STPŎSÍC, Borko; STŎSÍC, Tatijana (Brazilian Journal of Biometrics, 2016)
In this paper we investigate the time series behavior on daily closing prices of some commodities of Brazilian agribusiness. We analyze the behavior of multifractality and complexity of the series recorded between 2006 and 2014. We use the Sample Entropy and Cross-Sample Entropy methods to analyze the complexity and propose the Sample Entropy method in a moving time window to assess the dynamics of the complexity of these series. We also investigate the multifractality using the Multifractal Detrended Fluctuation Analysis (MF-DFA) method. We conclude that both analyzes can be useful in assessing the dynamics of Brazilian agribusiness on the world economic scenario.